Low- and High-Attenuation Lung Volume in Quantitative Chest CT in Children without Lung Disease - Dimitrios Moutafidis; Maria Gavra; Sotirios Golfinopoulos; Antonios Kattamis; George Chrousos; Christina Kanaka-Gantenbein; Athanasios G. Kaditis (MDPI AG, 2021)
In contrast to studies of adults with emphysema, application of fixed thresholds to determine low- and high-attenuation areas (air-trapping and parenchymal lung disease) in pediatric quantitative chest CT is problematic. We aimed to assess age effects on: (i) mean lung attenuation (full inspiration); and (ii) low and high attenuation thresholds (LAT and HAT) defined as mean attenuation and 1 SD below and above mean, respectively. Chest CTs from children aged 6-17 years without abnormalities were retrieved, and histograms of attenuation coefficients were analyzed. Eighty examinations were included. Inverse functions described relationships between age and mean lung attenuation, LAT or HAT (p < 0.0001). Predicted value for LAT decreased from −846 HU in 6-year-old to −950 HU in 13- to 17-year-old subjects (cut-off value for assessing emphysema in adults). %TLCCT with low attenuation correlated with age (rs = −0.31; p = 0.005) and was <5% for 9-17-year-old subjects. Inverse associations were demonstrated between: (i) %TLCCT with high attenuation and age (r2 = 0.49; p < 0.0001); (ii) %TLCCT with low attenuation and TLCCT (r2 = 0.47; p < 0.0001); (iii) %TLCCT with high attenuation and TLCCT (r2 = 0.76; p < 0.0001). In conclusion, quantitative analysis of chest CTs from children without lung disease can be used to define age-specific LAT and HAT for evaluation of pediatric lung disease severity.